Molecular status of PI3KCA, KRAS and BRAF in ovarian clear cell carcinoma: an analysis of 63 patients. Issue 12 (6th May 2016) - Zannoni, Gian Franco; Improta, Giuseppina; Pettinato, Angela; Brunelli, Chiara; Troncone, Giancarlo; Scambia, Giovanni; Fraggetta, Filippo
Abstract : Aims: To evaluate the incidence of PI3KCA, KRAS and BRAF mutations in primary ovarian clear cell carcinoma (OCCC). Methods: 63 consecutive patients, with a proven diagnosis of OCCC, according to WHO criteria, were included into the study. Pyrosequencing analysis of all three genes hotspot regions were performed on 2.5 µm sections of formalin-fixed paraffin-embedded tissue from primary OCCC. Results: PI3KCA mutations were found in 20/63 (32%) cases; KRAS mutations were found in 8/63 (13%); no BRAF V600 mutations were found. In particular, 12/20 mutations (60%) of PI3KCA were found in the exon 20, whereas the remaining eight cases presented mutations in exon 9 (8/20; 40%). KRAS pyrosequencing analysis revealed higher incidence of codon 12 mutations (7/8; 90%) than codon 13 mutations (1/8; 10%). In five cases (5/66; 8%), synchronous mutations, affecting PI3KCA and KRAS genes, were found. No differences were found in the distribution of hotspot mutations, according to the stage. Conclusions: The high frequency of PI3KCA mutations, the low rate of mutations in KRAS and the absence of mutations in BRAF, indicate a molecular signature of OCCCs different from other ovarian carcinomas. Detection of driver mutations, such as PI3KCA and KRAS, may be the basis for a targeted therapy, although the clinical and therapeutic implications of these findings have to be supported by further studies.